Angeli in Ognjenci - Ježovnik, Janoš (Jezik in slovstvo, 2016)
The article discusses the translations of Resian dialectal poetry into standard Slovenian. The thesis deals with Renato Quaglia's poems translated by Marko Kravos and published in the collection Baside, as well as in the publications Stara piščal and Pogled. The Resian dialect differs substantially from Slovenian standard language. Therefore, after a thorough preliminary elucidation of sociological and linguistic circumstances, an analysis of Resian dialect translation into Slovenian is presented.
Keywords: slovenska narečna književnost; slovenska poezija; narečna poezija; Resian dialect; rezijansko narečje; rezijanščina; prevodi v slovenščino